Self-esteem among oncology patients receiving chemotherapy in selected government state hospitals in Peninsular Malaysia - Sivaperumal, Vidthya (2018)
Background : Cancer is one of the leading causes of mortality in both developed and developing countries and is a major public health problem in the world today. According to the World Health Organization (WHO), by 2020 mortality due to cancer shall total up to above 11 million people worldwide. The GLOBOCAN 2012 project shows that approximately 14.1 million new cancer cases reported and 8.2 million deaths due to cancer occurred in 2012. While in Malaysia, death caused by cancer in 2008 was 20,100 and this increased to 21,700 in 2012. The most common treatment given for cancer is chemotherapy and it is known for its side effects Objectives: The aim of this research was to determine the self-esteem among oncology patients receiving chemotherapy in Malaysia and to determine the predictors that affect their self-esteem. The factors which were included in this study were socio-demographic profile, physical effects of chemotherapy, anxiety, depression and quality of life. Methodology: An analytical cross sectional study with a quantitative approach was designed and carried out in the oncology wards in 10 government hospitals with oncology facilities in Malaysia. A total of 953 respondents were selected. Data were collected via questionnaires which included questions on socio demographics, Physical Effects (Common Terminology Criteria for Adverse Events), Anxiety (Generalized Anxiety Disorder 7), Depression (Patient Health Questionnaire 9) and Quality of Life (The World Health Organization Quality of Life Instrument). Data were analysed using the Statistical Package for Social Sciences Software (version 22). Results: This study had 100% responds rate of 953 participants. The mean (SD) self-esteem was 22.67 (4.98). The maximum point for self-esteem score in the questionnaire used in this study is 40 with no cut off point. Score 22.67 is considered to be moderate self-esteem (wati et al, 2008). The predictors were age, gender, marital status, working, anxiety, depression, nausea, anemia, hair loss, skin and nail changes, overall quality of life and psychological domain of quality of life. Since there is an increasing trend of cancer diagnosis globally, the side effects of cancer treatment are most likely on the rise. This study provides baseline data of self-esteem among oncology patients undergoing chemotherapy which may be helpful to determine the proper support and guidance to be given to patients.